Le développement phonétique irrégulier dû à la fréquence - Ma¡czak, Witold (My University, 2001)
Until now, irregular sound change due to frequency (first mentioned as early as 1846 by Diez, the founder of the comparative grammar of the Romance languages) has been considered as something sporadic, affecting only the vocabulary, whereas, to the present writer’s mind, irregular sound change due to frequency, which concerns also reductions in morphemes, especially in inflectional ones (which are even more frequently used than words), is the third essential factor of linguistic evolution, in addition to regular sound change and analogical development: in any text of any language, more or less one third of the words show an irregular sound change due to frequency.